Nauczanie kierowane jako metoda rozwijająca samodzielność oraz autonomię dzieci i młodzieży z głęboką niepełnosprawnością intelektualną - Cytowska, Beata (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2016)
The purpose of this article is to show the possibility of using conductive education system and its effectiveness in working with children and young people with profound intellectual disabilities attending rehabilitation – educational groups, in order to develop and form their self-reliance, and the grounds of autonomy. In the first part of text the author described the functioning of people with profound intellectual disabilities, pointing to their specific difficulties in the field of independent functioning. Then author showed the assumptions of conductive education system with regard to the objectives set by The Ministry of Education for rehabilitation-educational classes. Using of the possibilities inherent in the monographic method, the author presented rehabilitation-educational activities with the use of conductive education method, with particular attention to the aspects of the development of autonomy of children and young people with profound intellectual disabilities. The data for analysis and description was collected through the observation (direct, participatory and indirect – by video camera) of participants of rehabilitation – educational activities (15 persons), analysis of documentation (observation sheets and individual curriculums) and interviews with teachers of three rehabilitation – educational groups. Although it is difficult to determine the actual impact of Petö method on increase of self-reliance and autonomy of children and young people with profound intellectual disabilities, the collected information indicates the importance of the conductive education method – particularly in aspects of socialization, communication and agility.